Association of Paclitaxel Induced Neuropathy with Quality of Life of Patients with Non-Metastatic Breast Cancer - Masood, Masaba; Nadeem, Muhammad; Masood, Amna; Ali, Aamira; Tufail, Muhammad Umair (Pakistan Armed Forces Medical Journal, 2023)
Objective: To look for an association of Paclitaxel induced neuropathy with the quality of Life of patients with non-metastatic breast cancer.Study Design: Comparative cross-sectional study.Place and Duration of Study: Oncology Department, Combined Military Hospital, Rawalpindi Pakistan, from Nov 2021 to Feb 2022.Methodology: The study included one hundred and twenty patients with diagnosed non-metastatic breast cancer taking Paclitaxel chemotherapy for more than one month. Peripheral neurotoxicity was assessed by a consultant oncologist based on the Eastern Cooperative Oncology Group (ECOG) score. In addition, quality of Life was recorded with the help of the World Health Organization Quality of Life (WHOQOL)-BREF scale in all the study participants and associated with the presence and severity of neuropathy.Results: Out of 120 non-metastatic breast cancer patients using Paclitaxel for more than one month included in the study, 113 (94.2%) were female, while 7(5.8%) were male. 52(48.3%) had good quality of Life, while 68(51.7%) had poor quality of Life. 34(28.3%) had Grade-0 neuropathy, 54 (45%) had Grade-I, 30(25%) had Grade-II, and 2(1.6%) had Grade-III neuropathy.Statistical analysis showed that the presence and severity of neurotoxicity had a statistically significant relationship with poor quality of Life (p-value=0.001).Conclusion: Many patients having breast cancer using Paclitaxel had the presence of neuropathy. The presence and severity of neuropathy are strongly associated with poor quality of Life in patients included in our study.Keywords: Breast cancer, Neurotoxicity, Paclitaxel, Quality of life.